Perspectives surrounding bayanihan as an indigenous coping strategy a phenomenological study on relief campaigns conducted after typhoons amidst the COVID-19 pandemic - Quimsing, Anna Joaquine C.; Quebec, Maya Ysidrea Y.; Gecera, Eunice; Lubang, Felicia Cecille T. (2023)
The objective of this study is to determine the perspectives surrounding bayanihan. This study aims to explore the meaning of bayanihan for volunteers, its manifestations, potentials, and limitations in post-typhoon recovery during the COVID-19 pandemic. This research contributes to the current literature by expounding upon the understanding of bayanihan as an indigenous coping strategy, and how it might affect the context of disaster recovery and rehabilitation practices. The research utilizes a phenomenological design and the theory of Kapwa by Virgilio Enriquez as a lens. The data employs a multi-method approach, utilizing three focus group discussions and three interviews; consisting of nine members of different types of organizations and three key informants, respectively. The selection of the participants was through purposive sampling. The findings of this study include the following: (1) bayanihan is an inherent Filipino trait that involves helping through collective action without expecting returns, (2) it exists as an indigenous coping mechanism manifested in relief campaigns conducted in response to diasters, (3) bayanihan facilitates post-typhoon recovery during the pandemic, (4) bayanihan has no end, and (5) bayanihan can be a disadvantage as it can foster a sense of dependence among government officials and beneficiaries. Overall, bayanihan appears to be a considerable indigenous coping mechanism as it aids the recovery of typhoon-affected individuals and communities. However, on its own, bayanihan is an insufficient coping nechanism. With such results, those who participate in bayanihan, its beneficiaries, and the government must cooperate to facilitate and hasten disaster recovery.